2018
DOI: 10.1016/j.watres.2018.08.030
|View full text |Cite
|
Sign up to set email alerts
|

Applying UV absorbance and fluorescence indices to estimate inactivation of bacteria and formation of bromate during ozonation of water and wastewater effluent

Abstract: Ozone is an effective oxidant and disinfectant commonly used for elimination of micropollutants and inactivation of resistant microbes. However, undesirable oxidation/disinfection byproducts such as bromate might form during ozonation. In this study, the UV absorbance and fluorescence indices were applied as surrogate indicators for predicting the inactivation of bacteria and formation of bromate during ozonation of water and wastewater effluents. The inactivation efficiencies of lab-cultured Escherichia coli … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(14 citation statements)
references
References 36 publications
0
14
0
Order By: Relevance
“…Therefore, dissolved ozone residual is often not a reliable parameter for real‐time control. Several researchers have investigated the potential of utilizing UVA 254 or UVT 254 for real‐time monitoring and control of ozonation systems (Wert et al ; Chys et al, ; Wu et al, ). Trends observed in the field confirmed that the UVA decrease or UVT increase is proportional to ozone dose or ozone:TOC ratio.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, dissolved ozone residual is often not a reliable parameter for real‐time control. Several researchers have investigated the potential of utilizing UVA 254 or UVT 254 for real‐time monitoring and control of ozonation systems (Wert et al ; Chys et al, ; Wu et al, ). Trends observed in the field confirmed that the UVA decrease or UVT increase is proportional to ozone dose or ozone:TOC ratio.…”
Section: Resultsmentioning
confidence: 99%
“…Advantages of utilizing UVA 254 or UVT 254 for ozonation process control are (a) UVA or UVT is expected to change with ozone dose or ozone:TOC ratio, and (b) online monitoring is available and more feasible than fluorescence and other methods. Investigators have attempted to correlate %UVA to CEC removal, DNA damage (as a measure of pathogen inactivation and bromate formation), and CEC and bulk organics removal (Chys et al, ; Wu et al, ). Because each study or project has had a specific ozone dose and process control strategy, applications of those correlations have been limited.…”
Section: Resultsmentioning
confidence: 99%
“…Ozone is an effective disinfectant that can be used for the inactivation of microbes, including resistant bacteria (Wu et al, 2018). Ultrasonic treatment can also be used to eliminate bacteria (Sarkinas et al, 2018).…”
Section: Resultsmentioning
confidence: 99%
“…A number of indicators deemed to be suitable for optimizing ozone doses have been proposed. These are based on O 3 /DOC (dissolved organic carbon) mass ratio, differential UV absorbance (e.g., ΔUVA254 & UVA280), differential total/component fluorescence (e.g., ΔTF) and electron donating capacity (Chon et al, 2015;Gerrity et al, 2012;Li et al 2016Li et al , 2017Wu et al, 2018). For online measurements, UV absorbance and fluorescence indices are most applicable, since miniaturized UV absorbance and fluorescence spectroscopy prototypes and deployment-ready devices that use UV light emitting diode have been developed (Li et al, 2016;Tedetti et al, 2013).…”
Section: U N C O R R E C T E D P R O O Fmentioning
confidence: 99%